SEDIMENTOLOGICAL AND PALEODE POSITIONAL STUDIES OFROCKS WITHIN THE MIDDLE BENUE TROUGH (FULafia Journal of Science and Technology, 2026)
Previous studies were focused on Albian to Turonian sediments of the middle Benue Trough, which lies within Keana and Awe sheet 232 NW respectively. The present study extends to areas around Lafia town (Sheet 231NW) whose sediments range from Albian to Maastrichtian. Detailed field mapping on a scale of 1:50,000 was carried out and during this exercise, lithostratigraphic successions in the study area was established. Stratigraphic study of the area indicates the occurrence of three formations namely; the fluvial Lafia Formation, the shallow marine Awgu Formation and the transitional Awe Formation. 12 samples were collected for granulometric analysis and 8 samples for Petrographic analysis. The Lafia Formation consists of ferruginous sandstone capping the section, clay and clayed intercalated with sands at the base. Petrography and sieve analysis revealed that the Ferruginous sandstone ranged from fine to medium grain. It is moderately sorted, strongly fine skewed and is subarkosic arenite. More than 60 % of the crystals are monocrystalline which is indicative of igneous provenance. The Awe Formation consists of fine-grained white sandstone, with some intercalations of white clay and laminated shale. The sandstones are fine-grained and poorly-moderately sorted which coupled with the bivariate plot that indicates a transitional condition between shallow marine and fluvial systems. The Awgu Formation consists of sandstones that are fine grained, very poorly sorted and strongly fine-skewed. The presence of ostracodes, echinoderms, and ammonites within the shaley limestone of the Awgu Formation is indicative of marine environment.
Keywords: Lafia; Ferrugenised; fluvial; subarkosic; provenance